Correndo pelas bordas? trajetórias educativas e laborais de jovens mulheres do audiovisual - Justino, Jeniffer Cristina Ferreira (Universidade Federal de São Carlos, 2024)
This investigation seeks to understand the relationships of young women working in the Audiovisual field—considering cinema, radio, TV, photography, and various ways of working in the area—identifying possible strategies for insertion and permanence in work and education, whether they are individual and/or collective. That is, the aim is to examine the narratives of these young women, particularly how they organize themselves to tackle the challenges of the labor world and identify the potential relationships these young women establish and/or have established in this context, whether through collectives, territory, workspaces, educational spaces, or any other shared environments. To achieve this, semi-structured interviews were conducted with five young women aged 20 to 30 in the city of São Paulo, with the purpose of listening to and documenting their narratives, as well as understanding the relationships they establish/established with the labor world of Audiovisual, their challenges, their aspirations, and the possible forms of organization for their insertion and permanence in the field amid the precariousness and transformations stemming from a capitalism that continually reinvents itself and contributes to the intensification of social asymmetries. In general, the investigation is based on contributions, reflections, and perspectives regarding Youth/Work, Gender/Work, and Audiovisual to understand the narratives of these young women in the Audiovisual field. Thus, considering the specificities and singularities of work in the Audiovisual sector, the results reveal that the insertion and permanence trajectories of the five young women are deeply impacted by inequalities of gender, race, and class. Their narratives highlight the importance of support networks and resistance strategies to confront the structural barriers of the sector. Despite precarity and intense work hours, these young women create their own routes 'through the margins,' their own bridges, transforming the audiovisual space into a place of struggle, survival, and social transformation. For them, the Audiovisual is both the poison and the antidote.
Running on the edges? educational and labor trajectories of young women in audiovisual
¿Corriendo por los bordes? trayectorias educativas y laborales de jóvenes mujeres en el audiovisual
Keywords: Jovens Mulheres; Juventude; Trabalho; Gênero; Audiovisual; Educação; Young Women; Youth; Work; Gender; Education; CIENCIAS HUMANAS::EDUCACAO